As Verbascoside Supplementation Affects Metabolic Profile, Oxidative Status, and Quality of Milk and Meat: The Studies on Donkeys - Angela Gabriella D’Alessandro; Giovanni Martemucci (Research Aspects in Agriculture and Veterinary Science Vol. 6, 2022)
The study reviewed some papers related to the dietary supplementation of verbascoside (VB), an antioxidant compound of natural origin, with the aims to highlight the effects on hematochemical parameters and oxidative status of donkeys and quality of their products, milk and meat. The VB supplementation resulted in decreased serum lipidic and hepatic profiles, and improved oxidative status in the lactating jennies, influencing, at the same way, their suckling foals. The quality of milk resulted affected in SFA, MUFA and vitamins A and E contents. On meat, the effects concerned the improving of oxidative stability during storage and the colour, taste and texture sensory traits. The findings of the study may represent a reference point for improving animal welfare and qualitative and nutraceutical characteristics of the products.